A recepção criativa de “L’Étranger” em “Meursault, contre-enquête” de Kamel Daoud - Pimentel, Gabriel Dias (2021)
The present work proposes to develop a brief analysis of the different forms of interpretation of the work L’Etranger (1942) by the Franco-Algerian writer Nobel Prize for Literature Albert Camus. Based on the panorama of his critical fortune, we enter into the analysis two works directly influenced by Camus, namely the novel Meursault, contre-enquête (2014) by the writer Kamel Daoud and the song As caravanas (2017) by the Brazilian multiartist Chico Buarque de Hollanda. In this analytical path, we will enter into how postmodern parody and fictional testimony are fundamental points in the work of Daoud and the critical reinterpretation of Brazilian social relations will be the song of Hollanda. Our theoretical foundation, in addition to the critical fortune of the source text of Camus, will be based on the theoretical basis of the author Linda Hutcheon (1985; 1991), to discuss her postmodernity, Márcio Seligmann-Silva (2005) and Beatriz Sarlo (2007) contributing to the status of testimony, among others authors who contributed in different ways to build the critical fortune of the three works worked and guide the interpretations defended during the dissertation.